The Role of Civil Society In Waste Management Through The Latanza Waste Bank In Karawang Regency - Putri Wahdah Hija Fajriah; Lukmanul Hakim; Evi Priyanti; Kariena Febriantin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The independent waste management program through the Waste Bank has become an alternative solution for the government and the community. The solution to reduce the increasing volume of waste that is getting out of control. Socialization of independent waste management through the Waste Bank is still being intensively carried out by the city and district governments. In addition to having a positive impact on the environment, in the process of managing it, the waste bank has a relationship mechanism and social network that has economic value. The Latanza Waste Bank can act as a dropping point for producers for products and product packaging that have expired. Some of the government's responsibility in waste management is also the responsibility of business actors. Aspects of waste management, if applied optimally at the Latanza Waste Bank, will help in the management of waste in Cikampek City. The application of the 3R principle as close as possible to the source of the waste is also expected to be able to solve the waste problem in an integrated and comprehensive manner, so that the ultimate goal of Indonesia's Waste Management policy can be implemented properly in this case Civil Society has a role in overcoming the waste problem in Karawang Regency by establishing the Latanza Waste Bank.